Effects of Paraoxonase 1 gene polymorphisms on organophosphate insecticide metabolism in Japanese pest control workers - Sato, Hirotaka; Ito, Yuki; Ueyama, Jun; Kano, Yuya; Arakawa, Tomoya; Gotoh, Masahiro; Kondo, Takaaki; Sugiura, Yuka; Saito, Isao; Shibata, Eiji; Kamijima, Michihiro (Journal of Occupational Health, 2016)
Abstract: Objectives: Paraoxonase 1 (PON1) in serum detoxifies organophosphate (OP) insecticides by hydrolysis. The present cross-sectional study aimed to clarify the relationship between PON1 single nucleotide polymorphisms (SNPs) and enzyme activities or OP metabolite concentrations in urine of workers occupationally exposed to low-level OPs. Methods: Among 283 workers in 10 pest control companies located in central Japan who underwent checkups, 230 subjects (male 199, female 31, average age 38.9 +- 11.1 years old) participated in the study. Q192R and L55M polymorphisms were determined by TaqMan assay. PON1 activity was measured using fenitrothion (FNT) oxon, chlorpyrifos-methyl (CPM) oxon, chlorpyrifos (CP) oxon, and phenyl acetate as substrates. Urinary OP metabolite concentrations were measured with gas chromatography-mass spectrometry. Results: The maximum differences in enzyme activities between individuals were 64.6-, 6.3-, 7.7-, and 2.0-fold for FNT oxonase, CPM oxonase, CP oxonase, and arylesterase (ARE), respectively. The activities of CPM oxonase and ARE in workers having the RR genotype were 53.5% and 18.2% lower than in those with the QQ genotype, respectively. CP oxonase activity was 15.0% lower in those having the M allele (LM + MM compared with LL). Urinary metabolite concentrations were not associated with PON1 polymorphisms, but negative associations were observed between the concentrations and activities of FNT oxonase and ARE. Conclusions: While PON1 SNPs can explain differences in catalytic activities toward some OPs, differences in urinary concentrations of OP metabolites are not attributable to PON1 SNPs but instead are attributable to its serum activities. Its serum activities might be more sensitive biomarkers for estimation of individual susceptibility to OP toxicities.